The Journal of Global Neurosurgery - Esene , Ignatius; Park, Kee B (JOURNAL OF GLOBAL NEUROSURGERY, 2021)
1 | WHAT IS GLOBAL NEUROSURGERY? The Global Neurosurgery Committee of the World Federation of Neurosurgical Societies defines Global Neurosurgery as “the clinical and public health practice of neurosurgery with the primary purpose of ensuring timely, safe, and affordable neurosurgical care to all who need it”(1). The definition weaves the values of equity, social justice, and inclusivity through the fabric of the traditional characteristics that define modern neurosurgery, such as excellence, technical mastery, integrity, and compassion. The recent addition of the global health dimension and the accompanying scientific and systems approach to address the unmet neurosurgical needs in the world has galvanized our profession, stimulated academic inquiry, and inspired many who wish to enter it. One only needs to see the explosive number of publications using the terms “global neurosurgery” over the last few years as a proxy of academic interest (2) (figure 1).